Analysis of Mathematical Communication Skills of Grade X MA Students on the Material of Trigonometric Function Graphs Aided by Geogebrabook - Yustiani, Novita Rizki; Rosyadi, Alfiani Athma Putri; Cholily, Yus Mochamad (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
Mathematics is a supporting science for other branches of science as a medium for communicating mathematical problem solving. One of the abilities that must be possessed by students is the ability to communicate in trigonometry material. In this research, only 36.7% of students correctly identified the transformation of trigonometric function graphs in question number 9. However, there were some students whose explanations were not precise because their understanding of the material was not correct. The purpose of this study is to analyze the mathematical communication skills of grade X MA students in the material of trigonometric function graphs. In this research, a qualitative research type with a descriptive approach is used. The test of mathematical communication ability in writing is in the form of a test that is done independently and tested on 6 students with a group of 2 high ability students, 2 medium ability students, and 2 ability students with the need for further guidance. While the test of mathematical communication skills orally answered together through the interview method. The significance of this research is the students become more focused in learning because students are instructed to do activities by shifting the slider so that the intended graph is formed according to the instructions of the given problem. The conclusion drawn from the results of the research conducted is that mathematical communication in the material of trigonometric function graphs is relatively low, both in writing and orally. This is based on the percentage in the analysis test of mathematical communication skills in writing where students answered 10 out of 18 items had below 50% incorrect written response rates, compared to 8 other items that students could answer correctly with a score above 50%, while in the oral mathematical communication ability analysis test there are still misconceptions in every question asked. This is based on this research data that some students still answer the items incorrectly.